JENIS-JENIS SERANGGA HAMA YANG MENYERANG TANAMAN UBI JALAR (Ipomoea Batatas L) DI DISTRIK WAIBU KABUPATEN JAYAPURA - Lawalata, Jacob Julius; Wonda, Ikison (STIPER Santo Thomas Aquinas Jayapura, 2023)
Sweet potatoes (Ipomoea batatas), better known by the Papuan people as petatas, are a commodity that is widely consumed by the people as a source of carbohydrates to replace rice besides sago, especially in mountainous areas. There are many types of sweet potatoes in the Papua region, some of which are white, yellow, purple and some even have batik-like colors. Sweet potatoes are often used in stone burning activities, traditional ceremonies as well as for people's daily consumption. Insect pests are animals that damage crops and can cause losses for farmers because they can reduce crop production levels and the level of income, farmers will always pay attention and manage it well so that it is always at the economic threshold so that they can increase the production of agricultural products because when these pests are not managed well then the yield will decrease. Information and knowledge about the types of insect pests that attack plants sweet potatoes in a place or field of sweet potatoes play an important role in determining the control measures that will be carried out so that the control can be effective in controlling insect pests and increasing the production of cultivated plants. This research aims to inventory the types of insect pests that attack sweet potato plants (Ipomoea batatas L) in the Waibu district, Jayapura Regency. This research was carried out in farmers' sweet potato plantations in Doyo Baru Village, Waibu District, Jayapura Regency in September - October 2022, observation or data collection was carried out using the observation or direct observation method. Pest insects are obtained by catching them directly or using insect nets. Insect pests that attack sweet potato plants in the Waibu District, Jayapura Regency are turtle beetles (Aspidomorpha miliaris), leaf rollers (Brachmia convolvuli), armyworms (Spodoptera litura), whitefly (Bemisia tabaci), green grasshopper (Atractomorpha crenulata) and sweet potato beetle (Cylas formicarius).